Correlation between antibiotic-induced feeding depression and body size reduction in zooplankton (rotifer, Brachionus calyciflorus): Neural response and digestive enzyme inhibition. (March 2019) - Yan, Zhengyu; Yang, Qiulian; Wang, Xiao; Torres, Oscar Lopez; Tang, Shengkai; Zhang, Shenghu; Guo, Ruixin; Chen, Jianqiu
Abstract: The study analyzed the correlation between the antibiotic-induced feeding depression and body size reduction in rotifer, Brachionus calyciflorus, involving exposure, post-exposure and re-exposure periods. The filtration and ingestion rates of the rotifers were inhibited in these three exposure periods at any given concentration of the antibiotic sulfamethazine (SMZ). As food for rotifer, the cell size of the green algae was unchanged, which indicated that it could not drive feeding depression. Secondly, several corresponding physiological responses were considered. Reactive oxygen species (ROS) levels increased in the post-exposure and the re-exposure; acetylcholinesterase (AChE) activity was significantly decreased in the exposure and the re-exposure, whereas it was induced in the post-exposure. The activities of amylase and lipase were always inhibited in these three exposure periods. Additionally, significant decreases in lorica length, width and biovolume of rotifers occurred after the feeding depression. Statistical analysis indicated a positive correlation between the activity of the digestive enzyme and the body size. Our results demonstrated that SMZ could influence the neurotransmission, inhibit the activity of the digestive enzyme, and finally result in body size reduction. These results provided an integrated perspective on assessing the toxicity effects of antibiotic in non-lethal dosage on the feeding behavior of non-target aquatic organisms. Graphical abstract: Image Highlights: SMZ induced food-intake suppression in rotifer in any exposure period. Algal cell size unchanged and therefore not drove feeding depression. Response of ROS intensified from exposure, post-exposure to re-exposure. AChE activity was stimulated even if the exposure was ended. Inhibited amylase and lipase activities are correlate with shrunken body size.